A Scoring System for the Assessment of Angiographic Findings in Non-Occlusive Mesenteric Ischemia (NOMI) - Minko, P.; Groesdonk, H.; Stroeder, J.; Miodek, J.; Graeber, S.; Bücker, A.; Schäfers, H. J.; Katoh, M. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2012)
Purpose: To establish a standardized scoring system for angiographic findings in patients with non-occlusive mesenteric ischemia (NOMI). Materials and Methods: In 36 patients (mean age: 72 years), 53 angiographies of the superior mesenteric artery (SMA) were performed for suspected NOMI after cardiac or major aortic surgery. All examinations were performed using a standardized DSA technique. Two experienced radiologists performed a consensus reading blinded to the clinical information, on two occasions with an interval of two weeks. In order to investigate the reproducibility of the criteria, the images were assessed once by an intensivist and a medical student. Image analysis was performed with respect to vessel morphology, reflux of contrast medium into the aorta, small bowel parenchymal contrast enhancement and distension and the delay between arterial injection and portal vein filling. Results: Almost perfect intra-observer correlation was obtained for the assessment of the contrast medium reflux (κ = 0.82) and substantial correlation for the time of portal vein filling (κ = 0.66). Moderate correlations were obtained for the vessel morphology (κ = 0.51), small bowel enhancement (κ = 0.63) and distension (κ = 0.53). Contrast medium reflux into the aorta (κ = 0.77 and 0.63) and the time of portal vein filling (κ = 0.42 and 0.58) resulted in the highest inter-observer correlations between the radiologists and the intensivist as well as the radiologists and the student. Conclusion: In patients with suspected NOMI, using our scoring system yields high intra- and inter-observer correlations, allowing a standardized evaluation of angiographic findings.
Keywords: abdomen; angiography; diagnostic radiology; ischemia/infarction; obstruction/occlusion